2021
DOI: 10.1155/2021/5573644
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Potato Seedlings at Different Storage Temperatures

Abstract: In order to promote the storage and growth of potato seedlings, the antioxidant activities of potato seedlings at different storage temperatures were analyzed. The antioxidant activities of potato seedlings at two different temperatures were compared. In addition, the effects of high temperature and normal temperature on the growth phenotype and antioxidant system physiological indexes of potato seedlings were analyzed by high temperature treatment. According to the significant change characteristics of SOD ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…Pigment contents, ROS, REC, MDA, CAT and POD were observed in the same quadrant, and ANOVA results showed an increasing trend under upwelling stress suggesting some homogeneity in the regulatory mechanism of these traits in the face of upwelling stress for three mangrove species (Behrooz Sarabi, 2022). Previous studies showed that plants respond differently to different temperatures under chilling stress (Ok et al, 2020;Wang et al, 2021). In our research, none of the mangrove species exhibited markedly different responses to variations in upwelling water temperatures, indicating that mangroves are not sensitive to temperature variations in upwelling stress compared to low air or water temperatures.…”
Section: Species Effect and Temperature Effect Under Upwelling Stresscontrasting
confidence: 42%
“…Pigment contents, ROS, REC, MDA, CAT and POD were observed in the same quadrant, and ANOVA results showed an increasing trend under upwelling stress suggesting some homogeneity in the regulatory mechanism of these traits in the face of upwelling stress for three mangrove species (Behrooz Sarabi, 2022). Previous studies showed that plants respond differently to different temperatures under chilling stress (Ok et al, 2020;Wang et al, 2021). In our research, none of the mangrove species exhibited markedly different responses to variations in upwelling water temperatures, indicating that mangroves are not sensitive to temperature variations in upwelling stress compared to low air or water temperatures.…”
Section: Species Effect and Temperature Effect Under Upwelling Stresscontrasting
confidence: 42%
“…Potato (Solanum tuberosum L) is a crucial staple food in numerous countries, ranking fourth after rice, wheat, and corn. Globally, more than 2.1 × 10 8 ha are dedicated to potato cultivation (Volkogon et al, 2021;Wang et al, 2021). China, the world's largest potato producer, is followed by India and Russia.…”
Section: Introductionmentioning
confidence: 99%